Cultural Values in Acehnese Farming-Related Proverbs - Ibrahim, Ibnu Hajar; Usman, Jarjani (Indonesian Journal of Applied Linguistics, 2021)
Cultural values play a significant role in society as they determine what actions are best to do. In the Indonesian province of Aceh, there are many farming-related proverbs, or locally called hadih maja (HM), which have rich cultural values that have been transferred for generations in the society for centuries. However, research on cultural values in Acehnese farming-related HMs is scant. This study identifies and interprets the cultural values embedded in the Acehnese proverbs. The data sources emanate from documents (books and dictionaries) and fourteen purposively selected respondents in Aceh, collected through document analysis and Focus Group Interview (FGI). The data were then analyzed using qualitative descriptive techniques. The results reveal eight cultural values embedded in Acehnese farming-related proverbs (HMs): trustworthiness, consistency, usefulness, patience, diligence, discipline, responsibility, and gratefulness. The cultural values emanating from the proverbs are crucial for shaping people's personal and cultural identities in Aceh. This study concludes that the farming-related proverbs in the Acehnese language have many positive cultural values essential for life that need to be incorporated into the school curricula to make students competent in understanding and using them in and for their lives.